Untangling Infinite Regress and the Origins of Capability. (January 2020) - Hallberg, Niklas L.; Felin, Teppo
We argue that strategic management in general—and capability theory in particular—suffers from problems of infinite regress that can be traced to an unsatisfactory specification of initial conditions. We argue, first, that this has led to an overemphasis on path dependence, experience, and history, without sufficient attention on initial conditions: more proximate, decision-oriented punctuation points that can be used for better theoretical explanation. Second, we show how the initial conditions of theories are often not distinctively different from what is being explained, which prevents theory from providing credible specifications of causal mechanisms. Third, we highlight how the regress problem has led to a relatively casual borrowing of concepts from neighboring disciplines, which has created a mismatch between the aims of management theory and relevance to practice. We suggest research heuristics for how to deal with infinite regress problems, in order to develop more rigorous and relevant theories of capability and strategic management.